The Effect of Price, Product Quality and Brand Image on the Purchase Decision Process of Telkomsel Sim Card - Taufik, Ahmad (Universitas Mercu Buana, 2020)
The reseacrh is to know the influence of price, product quality and brand image to purchase decision. The object of this research is Telkomsel users in Ciledug area. This research was conducted to 208 respondents. Data collection techniques using non probability methods with random sampling by using a quantitative descriptive approach. The result of this study indicate that price have a positive and significant effect on purchasing decision, product quality have a positve and significant effect on purchasing decision, and brand image have a positive and significant effect on purchasing decisions.